Chernobyl [videorecording (Blu-Ray)] - Mazin, Craig, 1971- (HBO Home Entertainment, 2019)
In April 1986, an explosion at the Chernobyl nuclear power plant in the Union of Soviet Socialist Republics becomes one of the world's worst man-made catastrophes, but brave men and women made incredible sacrifices to save Europe from unimaginable disaster. Dramatized from true events.